Sannazaro in Bembo: la ricezione dei "Sonetti et canzoni" nelle "Rime" del 1535 e 1548 (Quaderni di Gargnano, 2020)
Moving from the historical reconstruction of the events through which Pietro Bembo took possession of a copy of the editio princeps of Sannazaro’s poems, this paper investigates the intertextual relationships between the Sonetti et canzoni and the last two editions of Bembo’s Rime. Through the reading of some selected and significant texts, the research highlights the triangular relationship between Bembo’s poems, Sannazaro’s ones, and Petrarch’s Canzoniere, which is the constant point of reference for the lyrical exercise of both writers. Partendo dalla ricostruzione storica delle vicende tramite cui Bembo entrò in possesso di una copia della princeps delle rime di Sannazaro, il presente contributo vuole indagare il legame intertestuale tra i Sonetti e Canzoni e le ultime due edizioni delle Rime di Bembo, evidenziando, attraverso la lettura di alcuni testi significativi, il rapporto di triangolazione che si instaura tra i componimenti di Bembo, quelli di Sannazaro e il Canzoniere di Petrarca, punto di riferimento costante per l’esercizio lirico di entrambi i poeti.
Keywords: Sannazaro; Sonetti et canzoni; Bembo; Rime bembiane; 1535; 1548